The communication between ocular surface and nasal epithelia in 3d cell culture technology for translational research: A narrative review - Aydin, Malik; Dietrich, Jana; Witt, Joana; Finkbeiner, Maximiliane S.C.; Park, Jonas J.H.; Wirth, Stefan; Engeland, Christine E.; Paulsen, Friedrich; Ehrhardt, Anja (International Journal of Molecular Sciences, 2021)
There is a lack of knowledge regarding the connection between the ocular and nasal epithelia. This narrative review focuses on conjunctival, corneal, ultrastructural corneal stroma, and nasal epithelia as well as an introduction into their interconnections. We describe in detail the morphology and physiology of the ocular surface, the nasolacrimal ducts, and the nasal cavity. This knowledge provides a basis for functional studies and the development of relevant cell culture models that can be used to investigate the pathogenesis of diseases related to these complex structures. Moreover, we also provide a state‐of‐the‐art overview regarding the development of 3D culture models, which allow for addressing research questions in models resembling the in vivo situation. In particular, we give an overview of the current developments of corneal 3D and organoid models, as well as 3D cell culture models of epithelia with goblet cells (conjunctiva and nasal cavity). The benefits and shortcomings of these cell culture models are discussed. As examples for pathogens related to ocular and nasal epithelia, we discuss infections caused by adenovirus and measles virus. In addition to pathogens, also external triggers such as allergens can cause rhinoconjunctivitis. These diseases exemplify the interconnections between the ocular surface and nasal epithelia in a molecular and clinical context. With a final translational section on optical coherence tomography (OCT), we provide an overview about the applicability of this technique in basic research and clinical ophthalmology. The techniques presented herein will be instrumental in further elucidating the functional interrelations and crosstalk between ocular and nasal epithelia.
CRIS-Team Scopus Importer:2021-12-10
Keywords: 3D cell culture; Goblet cells; Infection; Nasal epithelium; Ocular surface epithelium